PENGARUH WORD OF MOUTH, DIGITAL MARKETING, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SERTA LOYALITAS KONSUMEN PADA TOKO PERHIASAN SARI INTAN ASEMBAGUS SITUBONDO - Agung Ade Darmawan; Minullah Minullah; Hendra Syahputra (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
This study aims to analyze the influence of Word of Mouth (WOM), Digital Marketing, and Service Quality on Purchase Decisions and Customer Loyalty, as well as to examine the indirect effects through Purchase Decisions as a mediating variable. The participants in this research were patrons of Sari Intan Jewelry Store located in Asembagus, Situbondo. Data analysis was performed utilizing a statistical method, incorporating hypothesis testing founded on original sample values, T-statistics, and P-values. The findings show that: (1) WOM does not significantly influence Purchase Decisions; (2) Digital Marketing positively influences Purchase Decisions significantly; (3) Service Quality does not significantly influence Purchase Decisions; (4) WOM significantly positively impacts Customer Loyalty; (5) Digital Marketing negatively impacts Customer Loyalty but not significantly; (6) Service Quality does not significantly influence Customer Loyalty; (7) Purchase Decisions do not significantly influence Customer Loyalty; and (8) Purchase Decisions do not mediate the impacts of WOM, Digital Marketing, and Service Quality on Customer Loyalty. In summary, Digital Marketing is the key element influencing buying choices, yet it doesn't automatically result in customer loyalty. In contrast, WOM plays a direct role in fostering customer loyalty without influencing purchase decisions. At the same time, Service Quality does not exhibit a notable impact on any of the dependent variables. These results are anticipated to act as a benchmark for Sari Intan Jewelry Store in developing strategies to boost sales and customer loyalty.